Pengenalan Fungsi Bendungan Sederhana Kepada Pemuda Setempat - Daeli, Serta Denius; Mendrofa, Kevin Berkat (CV. SINAR HOWUHOWU, 2025)
Water resources are essential for community life, especially in agriculture and domestic needs. However, there is still a lack of understanding among young people regarding sustainable water management. This community service activity aims to educate local youth about the concept, function, and benefits of simple dams in water resource management. The methods used include counseling, demonstrations, and field practice. The results show an increase in participants' understanding, from 35% before the activity to 85% afterward. Additionally, potential locations for simple dam construction were identified as an initial step for future implementation. This program is expected to encourage youth to play a more active role in sustainable water management and the preservation of water resources in their environment.